Analisis Teks Deskriptif pada Buku Pembelajaran Prigel Bahasa Jawa Kelas X Terbitan Erlangga - Putri, Shinta Widyanti; Sulanjari, Bambang (Kaloka Jurnal Pendidikan Bahasa dan Sastra Daerah, 2022)
The Feasibility of a Descriptive Text in the Class X Javanese Prigel Learning Book Published by Erlangga AbstractThe purpose of this paper is to analyze the adequacy of a language in the Javanese descriptive text in the Javanese Prigel book whether it is good and worthy to be used as a learning text in the classroom later. This writing discusses the use of a text scope including: (1) Describing the purpose/social function in a descriptive text (2) Describing the stages in a descriptive text (3) Describing a linguistic feature in a descriptive text entitled sego megono . Data collection techniques used are reading and writing techniques and data analysis techniques using qualitative methods and descriptive analysis techniques which include description, classification and analysis. The results of this study are to find out in the descriptive text entitled sego megono whether it is feasible to be included in a study and whether the text already has a social function, stages, and linguistic characteristics in the text. Keywords: language, description, social function text, social stages, linguistic features